Personal Inviolability of Members of the Diplomatic Mission: current issues of international law - A. Al. Nagieva (Московский журнал международного права, 2022)
INTRODUCTION. Te establishment of diplomatic relations between States, among other mutual obligations of the parties, is based on the duty of the receiving State to provide appropriate conditions for the efcient performance of the functions of diplomatic mission. To this end, the authorities of the receiving State undertake to ensure respect for the full range of diplomatic immunities and privileges provided both in relation to the mission itself and in relation to diplomatic agents and members of their families. Te members of the diplomatic mission, in turn, undertake not to abuse the special legal status in the receiving State and not to take actions that entail interference in the internal aﬀairs of the receiving State, undermining the security of the latter and going beyond the ofcial actions of the diplomatic mission. However, the diplomatic practice abounds in examples of massive violations of diplomatic immunities and privileges, both by the authorities of the receiving State and third parties, and by the carriers of these immunities and privileges themselves. A special place among these violations is given to the violation of the personal inviolability of diplomatic agents. Te article examines the legal nature of the immunity of personal inviolability, acts of violations in relation to this immunity and the measures taken by states to provide full protection to members of a diplomatic mission and their families.MATERIALS AND METHODS. In the course of the study, international treaties applicable to the institution of diplomatic immunities and privileges were used, such as: Havana Conventions of 1928, Vienna Convention on diplomatic relations 1961, Vienna Convention on consular relations 1963, Convention on special missions 1969, Convention on the prevention and punishment of crimes against internationally protected persons, including diplomatic agents 1973, the Vienna Convention on the representation of states in their relations with international organizations of a universal character 1975, scientific works on diplomatic and consular law by domestic and foreign authors, as well as judgments concerning violations of diplomatic immunities and privileges. Te methodological basis of the research was formed by the following general scientifc techniques: analysis, synthesis, induction, deduction, comparison, classifcation, systematization, forecasting. Were applied and such specifc scientifc methods as formal legal and comparative legal.RESEARCH RESULTS. Te article provides a comprehensive analysis of the practice of granting and observing diplomatic immunities and privileges, based on the provisions of international treaties and acts of national law of some states. Particular attention is paid to cases of violation of diplomatic immunities and privileges and measures taken by states to prevent similar violations in the future.DISCUSSION AND CONCLUSIONS. According to the results of the research, it can be argued that there is a very dangerous tendency in the use of diplomatic immunities and privileges as a weapon of inﬂuence on states. It is necessary to develop new measures to ensure full protection of foreign bodies of external relations and their members, to strengthen domestic control over the observance of the legal status, immunities and privileges of these bodies and their members, as well as to strengthen cooperation between states to counter acts of violation directed against internationally protected persons.